Predatory publishing and global scholarly communications - Berger, Monica (Chicago : Association of College and Research Libraries, 2024)
'Predatory publishing is a complex problem that harms a broad array of stakeholders and concerns across the scholarly communications system. It shines a light on the inadequacies of scholarly assessment and related rewards systems, contributes to the marginalization of scholarship from less developed countries, and negatively impacts the acceptance of open access. To fix what is broken in scholarly communications, academic librarians must act as both teachers and advocates and partner with other stakeholders who have the agency to change how scholarship is produced, assessed, and rewarded. Predatory Publishing and Global Scholarly Communications is a unique and comprehensive exploration of predatory publishing in four parts: 1. Background; 2. Characteristics and Research; 3. The Geopolitics of Scholarly Publishing; and 4. Responses and Solutions. It examines the history of predatory publishing and basics of scholarly assessment; identifies types of research misconduct and unethical scholarly behaviors; provides critical context to predatory publishing and scholarly communications beyond the Global North; and offers structural and pedagogical solutions and teaching materials for librarians to use in their work with authors, students, faculty, and other stakeholders. Predatory Publishing and Global Scholarly Communications gives powerful insight into predatory publishing across the world, inside and outside of the library community, and provides tools for understanding and teaching its impact and contributing to its improvement'--
Includes notes and index.
Keywords: Predatory publishing -- Impact on scholarly communication; Scholarly publishing -- Ethics; Academic publishing -- International cooperation; Open access publishing -- Challenges and issues